2022
DOI: 10.3390/cells11132098
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cell Death by Activation of Hydroxycarboxylic Acid Receptor 1 (GPR81) in Retinal Explants

Abstract: Background: Progressive retinal ganglion cell (RGC) dysfunction and death are common characteristics of retinal neurodegenerative diseases. Recently, hydroxycarboxylic acid receptor 1 (HCA1R, GPR81) was identified as a key modulator of mitochondrial function and cell survival. Thus, we aimed to test whether activation of HCA1R with 3,5-Dihydroxybenzoic acid (DHBA) also promotes RGC survival and improves energy metabolism in mouse retinas. Methods: Retinal explants were treated with 5 mM of the HCA1R agonist, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Lactate has important functions in the nervous system. The extensive investigations of GPR81’s functions in the brain and retina have revealed many new mechanisms of the action of lactate and its role as a signaling molecule in the processes of angiogenesis in the nervous system, the regulation of neuronal excitation, and neuroprotection [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lactate has important functions in the nervous system. The extensive investigations of GPR81’s functions in the brain and retina have revealed many new mechanisms of the action of lactate and its role as a signaling molecule in the processes of angiogenesis in the nervous system, the regulation of neuronal excitation, and neuroprotection [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to using the GPR81 KO mice, DHBA, a widely used GPR81 agonist (Vohra et al 2022 ; Ohno et al 2018 ; Tassinari et al 2024 ), was used in the present study to investigate the pathological significance of GPR81. A previous study suggested that the carboxyl group, the 3-hydroxyl group, and the 5-hydroxyl group of DHBA are crucial for the molecular interactions between DHBA and GPR81, and treatment with DHBA inhibited the release of free fatty acid and glycerol in adipocytes, but the antilipolytic effects of DHBA were abolished in GPR81-deficient adipocytes (Liu et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed the expression of the lactate receptor GPR81 in Müller cells and retinal ganglion cells ( 55 ). Activation of GPR81 shields RGCs from glutamate-induced retinal degeneration and prevents visual impairment ( 81 ). GPR81 activation results in a decrease in cAMP levels in both neural and adipose tissues ( 55 ).…”
Section: Therapeutic Advantages Of Lactatementioning
confidence: 99%